How to improve top-quark tagging - Plehn, Tilman; Spannowsky, Michael; Takeuchi, Michihisa (Physical review. D, Particles, fields, gravitation, and cosmology, 2012)
In time for the first tests on LHC data we introduce a set of improvements and tests of purely kinematic top tagging algorithms. First, we show how different jet algorithms can be used for different transverse momentum regimes. Combining pruning and filtering in the reconstruction can enhance the signal over background ratio significantly, while larger jet radii only give minor improvements. Finally, bottom tagging can be added to the top tagger, but at least for the HEPTopTagger does not improve the kinematic selection algorithm.